LncRNA HOXA-AS2 Promotes Temozolomide Resistance in Glioblastoma by Regulated miR-302a-3p/IGF1 Axis. (21st November 2022) - Lin, Ligang; Lin, Da; Jin, Lingjiang; Wang, Junyou; Lin, Zheng; Zhang, Shuai; Lin, Gaojun
Abstract : Background . Glioblastoma (GBM) is a highly prevalent brain tumor characterized by high rates of morbidity, recurrence, and mortality. While temozolomide (TMZ) is commonly used as a first-line treatment for this cancer, the emergence of TMZ resistance limits its utility. The long noncoding RNA HOXA-AS2 reportedly drives GBM progression, but whether it can influence therapeutic resistance to TMZ has yet to be established. Methods . HOXA-AS2 expression was analyzed in TMZ-resistant and sensitive GBM tissue samples and cell lines by qPCR. A siRNA-based approach was used to knock down HOXA-AS2 in GBM cells, after which TMZ resistance was tested. Bioinformatics approaches were used to predict miRNA binding targets of HOXA-AS2, after which a series of luciferase reporter assay and rescue experiments with appropriate miRNA inhibitor/mimic constructs were performed to validate these predictions and to clarify the ability of HOXA-AS2 to regulate chemoresistant activity. Results . TMZ-resistant GBM patients and cell lines exhibited increased HOXA-AS2 expression that was correlated with worse overall survival. Knocking down HOXA-AS2 increased the sensitivity of resistant GBM cells to TMZ. miR-302a-3p was identified as a HOXA-AS2 target confirmed through luciferase reporter assays and rescue experiments, and IGF1 was further identified as a confirmed miR-302a-3p target. In addition, HOXA-AS2 knockdown resulted in a corresponding drop in IGF1 expression consistent with indirect regulation mediated by miR-302a-3p. Conclusion . In summary, these results highlight the role of HOXA-AS2 as a driver of TMZ resistance in GBM through its ability to regulate the miR-302a-3p/IGF1 signaling axis, highlighting this pathway as a promising target for the diagnosis, therapeutic sensitization, and/or treatment of affected patients.